A new species of bamboo-dwelling Ranitomeya (Anura: Dendrobatidae) from the Upper Purus River Basin of Brazil and Peru - Twomey, Evan; Melo-Sampaio, Paulo R.; Brown, Jason L.; Castroviejo-Fisher, Santiago; Gagliardi-Urrutia, Giussepe; Padial, José M.; Poblete, Roberto Gutierrez; Chaparro, Juan C. (Zootaxa, 2025)
A new species of Ranitomeya from Amazonian lowland forests in western Brazil and southeastern Peru is described and named. This species was formerly considered to be an outlying population of R. sirensis on the far eastern periphery of its geographic distribution. We analyze new and existing phylogenomic data and infer that the new species is not part of, or closely related to R. sirensis, but is sister to a clade including R. aetherea, R. aquamarina, R. cyanovittata, R. flavovittata, and R. yavaricola. The new species can be distinguished from species in its sister clade by its color pattern (yellow dorsal stripes, finely spotted ventral pattern, and a distinctive black band separating the gular and belly regions), and from R. sirensis by the presence/absence of a ventral color patch (absent in the new species, present in R. sirensis). Calls of the new species are longer in duration, with more pulses per call, and a slightly higher pulse rate, than any of the species in its sister clade for which call data are available. The new species is strongly associated with native Guadua bamboo, which it uses for reproduction. Based on museum records the new species also occurs in northern Bolivia. Unlike other close relatives, which are mostly monogamous, males of the new species appear to be polygynous, recruiting multiple females per breeding site.